RI 3827 Determination of the Size Distribution of Fine Coal Particles by the Electron Microscope - J. T. McCartney (The National Institute for Occupational Safety and Health (NIOSH), 1945)
"INTRODUCTION The surface areas of the finest fractions of a pulverized material are disproportionately larger than their weights. For instance, Pesrott and Kinney 3/ showed that, in a sample of minus 200-mesh coal, particles that are about 2 microns in diameter represent 15 percent of the entire surface area but only 1.5 percent of the total weight. Because the sur- face area is the dominating factor in the behavior of finely divided materials in many practical processes, the role of the finest particles is of great importance. The oxidation and combustion of pulverized coal, both in the dry form and in suspension in oils, and the hydrogenation to fluid hydrocarbons of mixtures of pulverized coal and heavy oil are reactions in which the surface area of the coal particles has considerable influence. This investigation of the size distribution of fine coal particles was conducted with the hope that such processes would thereby be better understood. The results should also be of value in the study of the crushing and fracture of coal."